Critique of Repetition in ʿUlūm al-Qurʾān Studies: Between Classical Tradition and Academic Stagnation - Zulfikar, Zaky Zimmatillah; Farhani Azkia; Danial Fayyadl (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract This paper examines the problem of repetition in classical ʿUlūm al-Qurʾān studies and its implications for the development of contemporary scholarship. Repetition rooted in authoritative works such as al-Burhān by al-Zarkashī and al-Itqān by al-Suyūṭī initially functioned as a mechanism of knowledge preservation. However, in later developments, uncritical repetition gave rise to epistemological stagnation and restricted the space for ijtihād. The problem became more complex with the sacralization of classical works, which led academic discourse into the canonization of old narratives. This study employs a qualitative library research method with a descriptive-analytical approach to analyze both classical and contemporary literature. The analysis reveals that repetition in ʿUlūm al-Qurʾān has contributed to the creation of an academic comfort zone, where curricula and discourses remain focused on old issues without the courage to adapt to modern challenges. The paper concludes that revitalizing ʿUlūm al-Qurʾān requires methodological courage to break free from the cycle of repetition. It highlights the contemporary approach of Ma‘na Cum Maghza as a constructive offer to restore ʿUlūm al-Qurʾān as a dynamic, critical, and relevant discipline for contemporary human concerns. Keywords: ʿUlūm al-Qurʾān; Repetition; Revitalization; Sacralization; Stagnation.   Abstrak Artikel ini mengkaji persoalan pengulangan dalam kajian ʿUlūm al-Qurʾān klasik serta implikasinya terhadap perkembangan khazanah keilmuan kontemporer. Pengulangan yang berakar pada karya otoritatif seperti al-Burhān karya al-Zarkashī dan al-Itqān karya al-Suyūṭī awalnya berfungsi sebagai mekanisme pelestarian pengetahuan. Namun, dalam perkembangan selanjutnya, pengulangan yang tidak kritis melahirkan stagnasi epistemologis dan mempersempit ruang ijtihād. Persoalan kian kompleks dengan menguatnya sakralisasi terhadap karya klasik, yang menjerumuskan wacana keilmuan ke dalam kanonisasi narasi lama. Penelitian ini menggunakan metode penelitian kepustakaan kualitatif dengan pendekatan deskriptif-analitis untuk menganalisis literatur klasik dan kontemporer. Hasil analisis menunjukkan bahwa pengulangan dalam ʿUlūm al-Qurʾān telah berkontribusi pada terciptanya zona nyaman akademik, di mana kurikulum dan wacana masih berkutat pada persoalan-persoalan lama tanpa keberanian untuk beradaptasi dengan tantangan kekinian. Artikel ini menyimpulkan bahwa revitalisasi ʿUlūm al-Qurʾān memerlukan keberanian metodologis untuk keluar dari siklus pengulangan. Pendekatan kontemporer Ma‘na Cum Maghza disoroti sebagai tawaran konstruktif untuk mengembalikan ʿUlūm al-Qurʾān sebagai disiplin ilmu yang dinamis, kritis, dan relevan dengan keprihatinan manusia masa kini. Kata Kunci: Pengulangan; Revitalisasi; Sakralisasi; Stagnasi; ʿUlūm al-Qurʾān.